Impulse transfer during sand impact with a cellular structure. (August 2015) - Holloman, Ryan L.; Deshpande, Vikram; Wadley, Haydn N.G.
Abstract: Compressible cellular metal sandwich structures made from a 3D assembly of square cross section 6061 T6 aluminum alloy tubes, and face sheets of the same alloy have been attached to a vertical pendulum and impacted by synthetic wet sand with an incident velocity of ∼300 ms −1 . The transmitted impulse of samples with thick (relatively rigid) and thin face sheets are compared to that transferred by an incompressible solid aluminum test block of the same dimensions. A discrete particle-based simulation method was used to simulate the experiments and to investigate the soil particle – structure interaction with the cellular structures. The simulated results agreed very well with experimental data; both showed that the impulse transferred to cellular structures with a 22 MPa core strength was 10–15% less than that transferred to a solid block of similar dimensions. However, the simulations reveal that the some of this apparent mitigation resulted from a subtle sand interaction between the bottom of the test structure and the sand box used for the tests. When this sand box effect was eliminated in the simulations, a small impulse reduction from cellular structures with thin face sheets was still observed. However, this was found to be a result of dynamic deflection of the edges of the front face sheet. When this effect was eliminated (by the use of a rigid front face), the simulations showed a small (5%) impulse reduction occurred for cellular structure whose compressive strength was much less than the pressure applied by the sand. This was a consequence of rapid core compression which increased the travel distance (and lateral spreading) of late arriving sand during the sand loading process. Weak cellular structures, that suffered significant crushing, also reduce the impulse transfer rate. Highlights: Measurements of momentum transfer to a cellular structure from a buried explosive. Particle based simulation method accurately predicts observations. A gap between the steel aperture and the samples front face influenced the tests. Reduced core crush strength resulted in a slight impulse reduction.